COMPARISON OF HEPATOPROTECTIVE ACTIVITY OF EUGENIA JAMBOLANA FRUIT WITH PUNICA GRANATUM FRUIT IN DIET INDUCED HYPERLIPIDEMIC RATS - Rabiea Bilal; Saba Tariq; Maryam Rashid et al. (Journal of University Medical & Dental College, 2017)
OBJECTIVE: To compare the hepatoprotective effects of Eugenia jambolana (EJ) fruit pulp with Punica granatum(PG) fruit in diet induced hyperlipidemic rats at the same dose level. METHODS: This experimental randomized control study was conducted on seventy five male albino rats over a period of 14 weeks in University of Health Sciences Lahore. Rats were divided into five groups labelled A, B, C, D and E. There were fifteen rats in each group. Group A was kept as normal control, groups B, C, D and E were given hyperlipidemic diet for the whole duration of study i.e. fourteen weeks. In group B no further intervention was done, group C and D were given ethanolic extract of Eugenia jambolana and Punica granatum in same dose of 200mg/kg respectively for eight weeks. Group E was given combination of both in same dose of 200mg/kg each of both extracts for same duration. Serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and triglycerides (TG) were measured at zero and six weeks to confirm hyperlipidemia. Alanine aminotransferase (ALT), Aspartate aminotransferase (AST) and Creatinine phosphokinase (CPK) were measured at zero, six and fourteen weeks to observe any significant change in their levels as compared to normal and hyperlipidemic rats at week zero and six respectively. RESULTS: At fourteen weeks, statistically no significant difference was found between groups A, C and E for serum ALT levels (p>0.05). For AST p>0.05 for group A vs E and C vs D only. CPK levels were not brought back to normal in any of the groups rather p>0.05 in B vs E. However it was significant (p<0.05) in all other groups for CPK. Baseline (at zero weeks) serum lipid profile, ALT, AST and CPK levels showed no significant difference in means of all the groups with value of p>0.05 on intergroup comparison. At six weeks rats in groups B,C,D and E were found to be higher lipid profile (p<0.05) with deranged ALT and CPK levels as compared to control group A (p<0.05). However serum AST levels were not significantly deranged at this time (p>0.05). Fifteen rats of group A had significant lower levels of serum TC, HDL-C, LDL-C, TG, ALT and CPK when compared to 60 rats of groups B, C, D and E (p<0.05). CONCLUSION: In male albino hyperlipidemic rats Eugenia jambolana fruit pulp extract alone and its combination with Punica granatum fruit pulp was equally effective in lowering serum ALT levels rather bringing them back to normal over a treatment period of eight weeks with continued hyperlipidemic diet. Serum AST levels were not deranged at six weeks but the levels remained normal with combination treatment only. However none of the treatment options could bring CPK levels back to normal rather one of the groups showed deranged CPK levels at the end of study.